MYCN mRNA degradation and cancer suppression by a selective small-molecule inhibitor in MYCN-amplified neuroblastoma - Liu, Tao; Gu, Lubing; Wu, Zhongzhi; Albadari, Najah; Li, Wei; Zhou, Muxiang (Frontiers in Oncology, 2022)
Amplification of the MYCN gene leads to its overexpression at both the mRNA and protein levels. Overexpression of MYCN mRNA may also have an important role in promoting neuroblastoma (NB) beyond the translation of MYCN protein. In the present study, we report a small molecule compound (MX25-1) that was able to bind to the 3’UTR of MYCN mRNA and induce MYCN mRNA degradation; this resulted in potent cell-growth inhibition and cell death specifically in MYCN-amplified or MYCN 3’UTR overexpressing NB cells. To evaluate the role of MYCN 3’UTR-mediated signals in contributing to the anticancer activity of MX25-1, we examined the status and activation of the tumor suppressor microRNA (miRNA) let-7, which is a target of MYCN 3’UTR in MYCN-amplified NB. We first observed that overexpression of MYCN mRNA was associated with high-level expression of the let-7 oncogenic targets DICER1, ARID3B, and HMGA2. Following MYCN mRNA degradation, the expression of DICER1, ARID3B, and HMGA2 was downregulated in MX25-1-treated cells. Inhibition of let-7 reversed the downregulation of these oncogenic mRNAs and significantly increased the resistance of NB cells to MX25-1. Our results from this study supported the notion that overexpression of MYCN mRNA due to gene amplification has an independent function in NB cell growth and disease progression and suggest that targeting MYCN mRNA may represent an attractive strategy for therapy of MYCN amplified NB, both by inhibiting MYCN’s cell-survival effects and activating the tumor-suppressor effect of let-7.